Influence of Different Landscape Configurations on Insect Pollinators of Important Horticultural Crops in a Western Himalayan Landscape - Khan, Susmita; Sinha, Bitapi; Uniyal, V.P. (Indian Forester, 2024)
Pollinators play critical roles in ecosystem stability and agricultural productivity, and their decline has become a global concern. One of the main reasons for pollinators decline is changing landscape configuration. We conducted this study in Kullu Valley of Himachal Pradesh, India to evaluate impact of varied landscape configuration on the diversity, richness, and abundance of insect pollinators in apple and plum orchards. Five different landscape configurations were considered for the study. The survey spanned 28 orchards across the valley during the blooming periods of 2021 and 2022. Standard sampling protocols were used to collect the pollinator specimen. Authors recorded a total of 108 insect species across 66 genera, 27 families and five orders (Hymenoptera, Lepidoptera, Diptera, Coleoptera, and Thysanoptera) from different orchards. Hymenoptera and Diptera were the most abundant pollinators in the study area. Pollinator richness and diversity were higher in orchards located within 1-km distance of natural forests and in lower elevations (>1500 meters). Orchards near large settlements, agricultural lands and complete modernised management practice showed comparative less pollinator diversity, richness, and abundance. This study demonstrates the influence of diverse land-use practices on pollinators on a landscape scale and provides insights for developing effective conservation strategies in the Himalaya.